(untitled) (Journal of Chitwan Medical College, 2026)
Introduction: Kangaroo Mother Care (KMC) is a cost-effective, evidence-based intervention for preterm and low birth weight (LBW) infants. This study explored the lived experiences of mothers practicing KMC in a neonatal ward in Nepal. Methods: A qualitative phenomenological study was conducted from Aug 2023 to Mar 2024 in the neonatal ward of Dhulikhel Hospital, Nepal. Following ethical approval, purposive sampling was used to recruit mothers of stable preterm and/or LBW newborns with ≥5 hours of KMC experience, continuing until data saturation. Data were collected through in-depth interviews using a semi-structured guide, audio-recorded, and transcribed verbatim. Transcripts were analysed using Colaizzi’s phenomenological method, involving immersion in the data, identification of significant statements, formulation of meanings, and clustering of themes to derive an exhaustive description. Results: Eight mothers participated. Thematic analysis revealed five interconnected themes: (1) recognition of KMC’s benefits for infant thermoregulation, weight gain, and bonding; (2) acknowledgment of its critical role in neonatal care; (3) reliance on nurses for procedural guidance and emotional reassurance; (4) initial hesitation rooted in fear of harming the fragile infant and lack of prior knowledge; and (5) an emotional progression from anxiety to confidence and attachment through practice. Collectively, these themes trace a maternal journey from uncertainty to empowered caregiving, facilitated by supportive clinical interactions. Conclusions: While mothers valued KMC, they overcame initial apprehension through supportive, nurse-led education and reassurance. This underscores the need to integrate structured educational and psychosocial support into nursing practice to enhance maternal confidence and adherence to KMC.